2018
DOI: 10.1073/pnas.1714795115
|View full text |Cite
|
Sign up to set email alerts
|

Physical and geometric constraints shape the labyrinth-like nasal cavity

Abstract: The nasal cavity is a vital component of the respiratory system that heats and humidifies inhaled air in all vertebrates. Despite this common function, the shapes of nasal cavities vary widely across animals. To understand this variability, we here connect nasal geometry to its function by theoretically studying the airflow and the associated scalar exchange that describes heating and humidification. We find that optimal geometries, which have minimal resistance for a given exchange efficiency, have a constant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In our model, L does not depend on the sniff wave form, and the velocity is proportional to the measured pressure: u|tP|t (Zwicker et al, 2018). The pressure changes due to the air flow have two main terms, the first one is due to the viscosity of the air is a narrow tube, i.e., it is a drag term which is proportional to the air velocity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our model, L does not depend on the sniff wave form, and the velocity is proportional to the measured pressure: u|tP|t (Zwicker et al, 2018). The pressure changes due to the air flow have two main terms, the first one is due to the viscosity of the air is a narrow tube, i.e., it is a drag term which is proportional to the air velocity.…”
Section: Resultsmentioning
confidence: 99%
“…We propose a very simple FD model for odor propagation in the nose. Although nasal cavities have complex geometries, the airflow within them is predominantly laminar and thus can be approximated using simple models (Zwicker et al, 2018). Obviously, our simple model does not capture all the subtleties of odor propagation, however, it does provide a reasonable explanation for the observed variability in sniff waveforms which contribute to variability in MT cell odor responses.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there has been considerable discussion and conflicting views regarding the presence of laminar or turbulent flow within the nose with studies involving physical models, mathematical models and numerical methods (29,30,(47)(48)(49)(50) , this study has provided a unique alternative method of analysis. In particular, the estimate of the critical Reynold number can be obtained from rhinomanometric data and therefore has the potential for clinical use where abnormal flow is suspected such as in those cases listed at the beginning of the introduction.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the human ability to orient to odors is not as highly developed as that of olfactory specialists, such as the domestic dog. First, the human internal nasal chamber is smaller than expected for a mammal of its body size (Zwicker et al, 2018). Its chamber lacks an olfactory recess, a feature found in the domestic dog that separates the olfactory air stream from the respiratory air stream.…”
Section: Human Olfactory Navigationmentioning
confidence: 98%
“…A new computational study of air flow in the mammalian nasal skeleton called even the assumption of turbulence into question. This model of the role of passage geometry in fluid mechanics concluded that the nasal passage is optimized to produce a laminar, not turbulent, airflow (Zwicker et al, 2018). This does not mean that the human nose does not condition air.…”
Section: Introductionmentioning
confidence: 99%